Progenitor cell secretory products exert additive renoprotective effects when combined with ace inhibitors in experimental CKD. (September 2016) - Kepecs, David M; Yuen, Darren A; Zhang, Yanling; Thai, Kerri; Connelly, Kim A; Gilbert, Richard E
Hypothesis/introduction: Renal fibrovascular injury often persists in chronic kidney disease patients treated with renin-angiotensin system blockers. Intriguingly, early outgrowth cell-derived factor infusion also inhibits chronic renal injury. We sought to determine whether early outgrowth cell-derived factor administration provides further renoprotection when added to renin-angiotensin system blockade. Materials and methods: Conditioned medium was generated by incubating rat early outgrowth cells with serum-free endothelial basal medium-2 to collect their secreted factors. Subtotal nephrectomy rats received enalapril 0.5 mg/L in drinking water or placebo, beginning 8 weeks post-surgery. Four weeks later, enalapril-treated rats received intravenous injections of either conditioned medium or control endothelial basal medium-2 for 2 weeks. Glomerular filtration rate, urinary protein excretion and renal structure were assessed 4 weeks later at 16 weeks post-surgery. Results: Enalapril-treated subtotal nephrectomy rats receiving control endothelial basal medium-2 injections experienced only partial renoprotection when compared to vehicle-treated subtotal nephrectomy rats. In contrast, conditioned medium infusion, when administered in addition to enalapril, attenuated the progression of renal dysfunction in subtotal nephrectomy rats, improving glomerular filtration rate and reducing proteinuria without affecting blood pressure. Conclusions: Early outgrowth cell-derived factors exert additive renoprotective effects on top of angiotensin-converting enzyme inhibitor therapy in experimental chronic kidney disease, providing the rationale for clinical trials of early outgrowth cell-based therapies for chronic kidney disease.